PENGENAAN SANKSI DAFTAR HITAM BAGI PELAKU PENGADAAN BARANG/JASA PEMERINTAH - Ira Kurnia Prasetia; Mohammad Saleh (Fakultas Hukum Universitas Narotama, 2023)
This paper aims to find out the forms of violation of the law in the procurement of government goods/services that can be subject to blacklist sanctions and to find out the legal consequences of imposing blacklist sanctions for perpetrators of government procurement of goods/services. In administering the government of a country, the state has the duty to carry out the life of the nation and state in order to improve the welfare of its people. To carry out this main task, one of which is that the government has the obligation to provide adequate facilities and infrastructure to be used by its people in various forms, whether in the form of goods, services or infrastructure development. The government can not always provide its own facilities and infrastructure needed by its people, for that the government seeks to carry out development through spending activities using third parties, namely providers/partners for procurement of goods and services as implementation of the application of sanctions for providers in the process of procurement of goods and services, one of which high integrity and able to help the government in realizing quality facilities and infrastructure for the community. From the government's point of view, the imposition of blacklist sanctions for election participants/providers aims to provide a deterrent effect to election participants/providers who are incompetent.Keywords: Procurement of government goods/services, blacklist sanctions, procurement actors